Bibliopsychological review of reading trends and book selection by young readers - ГОЛОВЧУК, Оксана; ГОЛЬЧА, Ангеліна (Київський національний університет імені Тараса Шевченка, 2025)
Background. The publication is based on a debate about how books influence emotional intelligence and overall effectiveness. For people aged 17-25, feeling the uniqueness of personal challenges is common in many life situations. Young individuals tend to exaggerate real dangers, so it is helpful to analyze whether a book that describes a similar situation acts as a "lifeline" for them. Does it serve as a source of energy and psychological stability? Are readers aware of the impact reading has on them? Methods. To gather primary data, an author's questionnaire was developed, and an indirect survey method was used. Part of the data was collected through direct surveys, such as interviews. Less than a third of the data came from emails and online surveys. We also analyzed sociological research on this topic, along with secondary data. Results. Patterns in mass communication and reading were identified and examined through bibliographic psychology methods. These include normalizing internal states after stress and receiving negative oral or written messages. The unique perceptions of reading among young people with a certain level of dreaminess and sensitivity were studied. Reading enhances emotional stability and emotional intelligence. In Ukraine, many respondents discovered the potential of bibliopsychology: in 2020, 8% of Ukrainians read literature daily, and by 2023, that number increased to 19%. The most popular genres are historical literature and psychological self-help books focused on overcoming anxiety. About a year after the enemy invasion, Ukrainians felt the need to understand reality and seek information about similar events in other societies and eras. This interest is reflected in autobiographical and historical works that explore the meaning of life. Conclusions. Developing a habit of regular reading influences human values, shapes consciousness and perceptions of reality, and strengthens independence from others' opinions. It involves the ability to stay aware and think critically despite widespread panic and pessimism. In modern Ukraine, reading acts as a mental weapon against despair and depression. It fosters an optimistic outlook on the world among young people, especially amid a flood of depressive media messages.

Вступ. Передумовою публікації став диспут щодо впливу книжок на стан емоційного інтелекту та загальну ефективність розумової діяльності людини. Для осіб віком 17–25 років у багатьох життєвих ситуаціях характерним є ефект відчуття унікальності особистих труднощів. Молода людина схильна перебільшувати реальну небезпеку, а тому доцільно проаналізувати, чи є книжка, яка описує подібну ситуацію, "рятувальним колом" для неї. Чи є джерелом енергії і психологічної стійкості? Чи усвідомлюють читачі ефект читання? Методи. Для збору первинної інформації сформовано авторську анкету й використано метод опосередкованого опитування. Частину інформації здобуто методом безпосереднього опитування – інтерв'юванням. Менш як третину інформації отримано за допомогою електронної пошти, методом комп'ютерного опитування. Проаналізовано соціологічні дослідження за визначеною тематикою та вторинні дані. Результати. Виявлено закономірності у сфері масових комунікацій та читання, які вирішуються посередництвом методики бібліопсихології. Йдеться про нормалізацію внутрішнього стану після стресу, отримання негативних усних чи письмових повідомлень. Досліджено особливості сприйняття прочитаного молодими людьми з певним рівнем мрійливості та чутливості. Читання підвищує емоційну стійкість та емоційний інтелект. В Україні можливості бібліопсихології відкрили для себе багато респондентів: якщо у 2020 р. щодня читали літературу 8 % українців, то у 2023 р. – 19 %. Найбільший попит має історична література та психологічні книжки про самодопомогу, подолання тривожності. Орієнтовно за рік після вторгнення ворога українці відчули потребу осмислити реальність, знайти інформацію про подібні події в інших суспільствах, в іншому часі. Про це свідчить інтерес до автобіографічних та історичних книжок, в основу сюжету яких покладено пошук сенсу життя. Висновки. Звичка регулярного читання впливає на визначення цінностей людини, формує свідомість і бачення реальності, посилює незалежність від думки оточення. Йдеться про здатність залишатися усвідомленим й критично мислити попри загальну паніку й песимізм. В сучасній Україні читання є ментальною зброєю проти зневіри і депресії. Воно сприяє формуванню у молоді оптимістичного бачення світу, що дуже важливо у час домінування депресивних інформаційних повідомлень.
Бібліопсихологічний огляд тенденцій читання й вибору книжок читачами у молодому віці
Keywords: bibliopsychology; psychology of reading; reader psychology; emotional intelligence; book selection psychology; бібліопсихологія; психологія читання; психологія читача; емоційний інтелект; психологія вибору книги; вплив читання